The Cambridge introduction to Theatre directing - Innes, Christopher, 1941-; Shevtsova, Maria (Cambridge : Cambridge University Press, 2013)
"This Introduction is an exciting journey through the different styles of theatre that twentieth-century and contemporary directors have created. It discusses artistic and political values, rehearsal methods and the diverging relationships with actors and designers, treatment of dramatic material and approaches to audiences. Offering a compelling analysis of theatrical practice, Christopher Innes and Maria Shevtsova explore the different rehearsal and staging principles and methods of such earlier groundbreaking figures as Stanislavsky, Meyerhold and Brecht, revising standard perspectives on their work, as well as analysing a diverse range of innovative contemporary directors, including Ariane Mnouchkine, Lev Dodin, Peter Brook, and Peter Sellars. While tracing the different roots of directorial practices across time, and discussing their artistic, cultural and political significance, the authors provide significant examples of the major directorial approaches and reveal comprehensive patterns in the craft of directing and the influence and collaborative relationships of directors"--
Includes bibliographical references (pages 253-275) and index.
Keywords: Theater -- Production and direction; Theater -- Production and direction -- History -- 20th century; Theatrical producers and directors; DRAMA / General